Idiopathic eosinophilia complicated with cryptococcal meningitis: a case report - Zhongshuo Liu; Ying Lou; Yingxiao Ji; Congying Zhao; Litao Li (Journal of International Medical Research)
Idiopathic eosinophilia, characterized by unexplained peripheral blood eosinophilia after ruling out secondary causes, is an extremely rare condition. Cryptococcal meningitis is a life-threatening opportunistic infection that primarily affects immunocompromised individuals, such as those with advanced AIDS or leukemia. In this report, we present a unique case of idiopathic eosinophilia concurrent with cryptococcal meningitis, which, to the best of our knowledge, is the first such case described globally.